CRISPR-Cas9 immune-evasive hESCs are rejected following transplantation into immunocompetent mice - Frederiksen, Henriette Reventlow; Glantz, Alexandra; Vøls, Kåre Kryger; Skov, Søren; Tveden-Nyborg, Pernille; Freude, Kristine; Doehn, Ulrik (Frontiers in Genome Editing, 2024)
While current stem cell therapies exhibit promising potential, the extended process of employing autologous cells and the necessity for donor-host matching to avert rejection of transplanted cells significantly limit the widespread applicability of these treatments. It would be highly advantageous to generate a pluripotent universal donor stem cell line that is immune evasive and therefore not restricted by the individual's immune system, enabling unlimited application within cell replacement therapies. Before such immune evasive stem cells can be moved forward to clinical trials, in vivo testing via transplantation experiments into immune competent animals would be the favorable approach in preceding preclinical testing. By using human stem cells in immune competent animals, results will be more translatable to a clinical setting, as no parts of the immune system have been altered, although in a xenogeneic setting. This way immune evasiveness, cell survival and unwanted proliferative effects can be assessed before clinical trials in humans. The current study presents the generation and characterization of three human embryonic stem cell lines (hESCs) for xenogeneic transplantation to immune competent mice. The major histocompatibility complexes I and IIencoding genes, B2M-and CIITA, have been deleted from the hESCs using CRISPR-Cas9 targeted gene replacement strategies and knockout. B2M was knocked out by insertion of murine CD47. Human secreted alkaline phosphatase (hSEAP) was inserted in a safe harbor site to track cells in vivo. The edited hESCs maintained their pluripotency, karyotypic normality, and stable expression of murine CD47 and hSEAP in vitro. In vivo transplantation of hESCs into immune competent BALB/c mice was successfully monitored by measuring hSEAP in blood samples. Nevertheless, transplantation of immune evasive hESCs resulted in complete rejection within 11 days, with clear immune infiltration of T-cells on day 8. Our results reveal that knockout of B2M and CIITA together with species specific expression of CD47 are insufficient to prevent rejection in an immune competent and xenogeneic context.